Analisis Fraud Triangle Untuk Mendeteksi Kecurangan Laporan Keuangan: - Septia Dwijayani; Nurzi Sebrina; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This study aims to obtain empirical evidence of fraud triangle in detecting fraudulent financial statements. The variabbles of fraud triangle are pressure, opportunity, and rasionalization then divided into six independent sub-variables. Namely financial stabilty which is proxied by asset change ratio (achange), personal financial need which is proxied by oship, external pressure which is proxied by the ratio of changes in debt (lev), financial targets that are proxied by ROA (ROA), the nature of industry that is proxied by inventory (inventory), effective monitoring that is proxied by the proportion of independent commissioners (ind), and rasionalization proxied by auditor change (auchange). The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017. the total sample of the study was 32 companies. Data analysis method uses logistic regression analysis. The results of this study indicate that financial stability variables, personal financial need, external pressure, nature of industry, effective monitoring, and rationalization have no effect on fraudulent financial statements. the results of this study can prove that financial targets have an effect on fraudulent financial statements. Further researchers can develop this research by adding sub-variables or using other proxies.